2014
DOI: 10.1186/1471-2296-15-123
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cardiovascular disease care in Ontario’s primary care practices: a cross sectional study examining differences in guideline adherence by patient sex

Abstract: BackgroundWomen are disproportionately affected by cardiovascular disease, often experiencing poorer outcomes following a cardiovascular event. Evidence points to inequities in processes of care as a potential contributing factor. This study sought to determine whether any sex differences exist in adherence to process of care guidelines for cardiovascular disease within primary care practices in Ontario, Canada.MethodsThis is a secondary analysis of pooled cross-sectional baseline data collected through a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…We identified sex disparities in achievement of CV treatment targets that are consistent with those seen in other cohorts [8][9][10]. Following publication of CV disease prevention guidelines specific to women [11], improved awareness of CV risk [12] and a one-third drop in age-adjusted death rates from coronary heart disease have been documented [13,14]; however, CV disease still outranks cancer, chronic lower respiratory disease, Alzheimer's disease and accidents for cause of death [15], and CV death rates in women aged 35-54 years are rising, presumably related to increasing rates of diabetes and obesity [14].…”
Section: Discussionsupporting
confidence: 72%
“…We identified sex disparities in achievement of CV treatment targets that are consistent with those seen in other cohorts [8][9][10]. Following publication of CV disease prevention guidelines specific to women [11], improved awareness of CV risk [12] and a one-third drop in age-adjusted death rates from coronary heart disease have been documented [13,14]; however, CV disease still outranks cancer, chronic lower respiratory disease, Alzheimer's disease and accidents for cause of death [15], and CV death rates in women aged 35-54 years are rising, presumably related to increasing rates of diabetes and obesity [14].…”
Section: Discussionsupporting
confidence: 72%
“…176 Disparities exist in regards to physician adherence to evidence based guidelines in the treatment of CVD and prescribing patterns have shown that women are less likely to be prescribed lipid lowering medications, antiplatelet agents, and beta-blockers at the time of hospital discharge than men. 290293 Hospitals participating in AHA Get With the Guidelines-CAD program have had increased rates of guideline adherence over a 5 year period regardless of gender and age. 294 This demonstrates the powerful impact quality improvement projects can have upon adherence, yet more data are necessary to determine if it will effect clinical outcomes.…”
Section: How Women Experience Ischemic Heart Diseasementioning
confidence: 99%
“…We focused on variation across these variables because age and gender disparities in quality of care have been described previously for chronic kidney disease and other related conditions. [31][32][33][34][35] We were also interested to see if there were changes over time. Finally, quality of care indicators for chronic kidney disease have been shown to vary based on chronic kidney disease stage.…”
Section: Statistical Analysesmentioning
confidence: 99%